2018
DOI: 10.1590/1980-57642018dn12-020010
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and cognitive performance of elderly in the context of social vulnerability

Abstract: Elderly who live in the context of social vulnerability have lower education and socioeconomic status.Objective:To analyze cognitive performance as a factor associated with frailty status in elderly living in contexts of social vulnerability.Methods:An exploratory, comparative, cross-sectional study using a quantitative method was conducted with elderly people registered at Social Assistance Reference Centers. A semi-structured interview, the Edmonton Frail Scale and Montreal Cognitive Assessment were applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
3
11
0
4
Order By: Relevance
“…This study demonstrates that, compared to non-frail older persons, those with frailty were more likely to be 80 years old or more, with a predominance of females, those living in nursing home, and those with low BMI, in accordance with other studies of frail elderly populations [ 19 , 20 ]. In addition, our findings indicate that frailty is mostly associated with cognitive impairment, risk of depression, altered nutritional status, and a decline in functional domains (ADL and TUG).…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrates that, compared to non-frail older persons, those with frailty were more likely to be 80 years old or more, with a predominance of females, those living in nursing home, and those with low BMI, in accordance with other studies of frail elderly populations [ 19 , 20 ]. In addition, our findings indicate that frailty is mostly associated with cognitive impairment, risk of depression, altered nutritional status, and a decline in functional domains (ADL and TUG).…”
Section: Discussionsupporting
confidence: 91%
“…Studies involving the Brazilian population of older adults report that women account for the majority of the samples, 6,24 which is likely due to the greater longevity of women compared to men, leading to a larger contingent of women aged 60 years or older. 25 This phenomenon is directly reflected in scientific studies involving samples recruited from the community.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A vulnerable individual is less likely to cope with stressful events, 4 which can lead to adverse health outcomes, such as functional decline, 5 and the aggravation of preexisting conditions, such as cognitive decline and physical frailty. 6 A slight decrease in cognitive function is expected during the aging process.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Frailty is a dynamic and multidimensional syndrome, that affects human functioning and is caused by a range of variables that increase the risk for dependency, institutionalization and death in old age. 16 , 17 Older adults with low education in Europe also seem to have a three times higher risk of being categorized as frail, as opposed to older adults with higher levels of education. 18 A Dutch study indicated that mature and older people who have completed higher education had consistently less overall frailty than people with primary or secondary education.…”
mentioning
confidence: 99%